If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2y + 3)(7y + 1) = 0 Reorder the terms: (3 + 2y)(7y + 1) = 0 Reorder the terms: (3 + 2y)(1 + 7y) = 0 Multiply (3 + 2y) * (1 + 7y) (3(1 + 7y) + 2y * (1 + 7y)) = 0 ((1 * 3 + 7y * 3) + 2y * (1 + 7y)) = 0 ((3 + 21y) + 2y * (1 + 7y)) = 0 (3 + 21y + (1 * 2y + 7y * 2y)) = 0 (3 + 21y + (2y + 14y2)) = 0 Combine like terms: 21y + 2y = 23y (3 + 23y + 14y2) = 0 Solving 3 + 23y + 14y2 = 0 Solving for variable 'y'. Factor a trinomial. (3 + 2y)(1 + 7y) = 0Subproblem 1
Set the factor '(3 + 2y)' equal to zero and attempt to solve: Simplifying 3 + 2y = 0 Solving 3 + 2y = 0 Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2y = 0 + -3 2y = 0 + -3 Combine like terms: 0 + -3 = -3 2y = -3 Divide each side by '2'. y = -1.5 Simplifying y = -1.5Subproblem 2
Set the factor '(1 + 7y)' equal to zero and attempt to solve: Simplifying 1 + 7y = 0 Solving 1 + 7y = 0 Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 7y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 7y = 0 + -1 7y = 0 + -1 Combine like terms: 0 + -1 = -1 7y = -1 Divide each side by '7'. y = -0.1428571429 Simplifying y = -0.1428571429Solution
y = {-1.5, -0.1428571429}
| lg(4x-2)=1 | | 10=v+1 | | X(x*x-1)=30 | | 14+x=8x | | 10a+9b=31 | | x(x*x+2x-1)-4x(-2x+3)= | | 3xy(5z-3)+(-15)xyz= | | 55n=500 | | -(x^3)+18*x^2-99*x+162=0 | | cos(x)-3sin(x)=1 | | 20=1/3A(4) | | cost-3sinx=1 | | (6a+2)(3a-2)= | | 9a+12= | | 2a^2*a^3b^-6/8a^2b^-4 | | (1-y)(1+y)= | | 3r-s=t | | x(4-6)= | | 87/0.01 | | 4x+3x+x-1=2x-7 | | 4x+3=2x+x-3 | | t=sqrt(2-4x^2) | | 4x+3x+1=2x+6 | | 4cos^2x-11cosx+6=0 | | 4x+14=10x+2 | | (12x-3)(x+6)= | | x+(x-9)=101 | | 4(3m+1)-2(2m+3)=3(m+4)+2+7 | | (8m+3n)(2m+5n)= | | 4x+9=10x+5 | | x^4+11x^2-900=0 | | (8m+3n)(x+6)= |